Analysis of Occupational Health and Safety Hazard Risk Using Hazard and Operability and Fault Tree Analysis Methods - Maharani, Cindi; Amri, Amri; Sayuti, Muhammad (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to identify the potential for occupational health and safety hazards using the Hazard and Operability (HAZOP) method and to provide recommendations for resolving the root causes of work accidents using Fault Tree Analysis (FTA). This study was conducted at PT. X, engaged in the plantation and processing of latex, is called Crumb Rubber. Based on data from 2022 to 2023, there are eight potential work accidents caused by several factors, such as the work environment, machines, and humans. The company has implemented an occupational health and safety program to support the safety of the company workforce. Even so, work accidents in the company still occur due to workers not being aware of the importance of occupational health and safety; this can be seen in workers who ignore their safety by not using complete personal protective equipment provided by the company. This still causes the potential for work accidents to occur. The study results show that the Hazard and Operability analysis revealed four different sources of danger that need attention: Low risk, such as split palms and slipping; Medium risk, including incidents such as sprained hands. High risk, including the potential for feet being stabbed by hooks, injured or cut hands, blistered and itchy hands, forklift accidents, and exposure to chemicals. Extreme risk is the potential for eye irritation. Based on the root causes of work accidents that have been observed using the Hazard and Operability method, recommendations were obtained using the Fault Tree Analysis method in the form of improving work attitudes, including creating a work health and safety training schedule, developing worksheets, and implementing attractive poster displays (visual displays). Recommendations for improving work environment conditions are recommended, especially managing puddles and chemical spills and optimizing machine maintenance.